Konsolidasi Metodologis Kalender Islam Internasional: Meneladani Intelektual Umar Bin Khattab dan Julius Caesar - Muh Rasywan Syarif; Naif (Direktorat Jenderal Bimbingan Masyarakat Islam, 2017)
Efforts to build an international Islamic calendar had been addressed in international scientific seminars since 1393 H / 1973 AD, most recently on 28-30 May 2016/21-23 Sya’ban 1437 H under the theme